Effect of freezing period on the quality of doe liver - Sharker, BC; Mia, N; Ali, MH; Hashem, MA; Rahman, MM; Khan, M (Meat Research, 2024)
The current study examined how the quality of doe liver was affected by a freezing period at -20°C. Raw, fresh doe liver was collected for this purpose and split into three treatment groups. On day 0, day 60, and day 120, they received treatment as T1, T2, and T3, respectively. Liver samples were frozen at (-20°C) and wrapped in plastic bags. For each treatment, the parameter studied were biochemical properties (TBARS), proximate component (DM, CP, EE, and Ash), physicochemical properties (pH, cooking loss, and water holding capacity), sensory attributes (color, taste, juiciness, and tenderness), and microbiological qualities (TCC, TVC, and TYMC). The findings demonstrated that as the number of storage days increased across all treatments, color, taste, juiciness, and tenderness all reduced (p<0.05). DM content was significantly increase (p<0.05), whereas crude protein, ether extract and ash were decreased with the increase of days of storage. pH and water holding capacity was decreased and cooking loss was increased among different treatments significantly (p<0.05). Biochemical properties such as TBARS were increased significantly (p<0.05). Microbial qualities such as TCC, TVC and TYMC values showed significantly (p<0.05) higher value with the increase of days of storage. From these findings the nutritive value of doe liver is less decreased during 60 days storage so it is acceptable for human consumption but the third treatment as 120 days, its quality is deteriorated with the increase of storage time.